Correction to: Evolution of body composition following successful kidney transplantation is strongly influenced by physical activity: results of the CORPOS study - Moreau, Karine; Desseix, Aurélie; Germain, Christine; Merville, Pierre; Couzi, Lionel; Thiébaut, Rodolphe; Chauveau, Philippe (BMC nephrology, 2021)
An amendment to this paper has been published and can be accessed via the original article.